Character Education in Mahfudzat as Self Control of Children's Lives at Sanggar Genius Ngrupit - Ibnu Hamdan Muzakki (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2024)
This research discusses the essence and urgency of education to grow the character of the nation's generation.  Amid technological advances and the development of globalization, Islamic education is the foundation for revising moral and moral values for one's personality. One source to instill these values is by teaching mahurat material to children. Because mahfudzat can provide positive energy to anyone who learns it. Mahfudzat teaches character values that can lift a person's motivation. So that in the daily lives of students, mahfudzat can become self-control of life. This research uses descriptive qualitative research, which conducts data analysis by enriching information, looking for relationships and finding patterns based on original data about mahfudzat material.  Data were obtained from interviews and observations at the research site. The data obtained is analyzed by compiling and describing it with theoretical foundations and relevant studies to draw conclusions. The findings in this study are the concept of character education, mahurat materials, the concept of mahfudzat learning in the Genius Ngrupit studio, and the analysis of character education in the mahfudzat material as self-control of children's lives in the saggar Genius Ngrupit.